Tethered-bilayer lipid membranes as a support for membrane-active peptides. (August 2001) - Cornell, B. A.; Krishna, G.; Osman, P. D.; Pace, R. D.; Wieczorek, L.
Abstract : An immunosensing device, comprising a lipid membrane incorporating ion channels tethered to the surface of a gold electrode, has been reported [Cornell, Braach-Maksvytis, King, Osman, Raguse, Wieczorek and Pace (1997) Nature (London) 387, 580–583]. The present article describes key steps in the assembly of the device and provides further evidence for its proposed sensing mechanism.